[Aerial View of Hafragilsfoss] - Streng, Evelyn Fiedler (1975)
Photograph of Hafragilsfoss Waterfall from above. A grey river stretches from the top left corner of the photograph to the waterfall at the bottom right of the photograph. Green grass and grey rocks surround the river, leading to dark, rocky plateaus on all sides.